A histological and morphometric assessment of endocrine and ductular proliferation in the adult rat pancreas using an occlusive pancreatic duct ligation model - Page, Benedict J. (Benedict John) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.